Formulation and Evaluation of Multilayered Tablets of Pioglitazone Hydrochloride and Metformin Hydrochloride - Chowdary, Y. Ankamma (J Pharm (Cairo), 2014)
In the treatment of type 2 diabetes mellitus a continuous therapy is required which is a more complex one. As in these patients there may be a defect in both insulin secretion and insulin action exists. Hence, the treatment depends on the pathophysiology and the disease state. In the present study, multilayered tablets of pioglitazone hydrochloride 15 mg and metformin hydrochloride 500 mg were prepared in an attempt for combination therapy for the treatment of type 2 diabetes mellitus. Pioglitazone HCl was formulated as immediate release layer to show immediate action by direct compression method using combination of superdisintegrants, namely, crospovidone and avicel PH 102. Crospovidone at 20% concentration showed good drug release profile at 2 hrs. Metformin HCl was formulated as controlled release layer to prolong the drug action by incorporating hydrophilic polymers such as HPMC K4M by direct compression method and guar gum by wet granulation method in order to sustain the drug release from the tablets and maintain its integrity so as to provide a suitable formulation. The multilayered tablets were prepared after carrying out the optimization of immediate release layer and were evaluated for various precompression and postcompression parameters. Formulation F13 showed 99.97% of pioglitazone release at 2 hrs in 0.1 N HCl and metformin showed 98.81% drug release at 10 hrs of dissolution in 6.8 pH phosphate buffer. The developed formulation is equivalent to innovator product in view of in vitro drug release profile. The results of all these evaluation tests are within the standards. The procedure followed for the formulation of these tablets was found to be reproducible and all the formulations were stable after accelerated stability studies. Hence, multilayered tablets of pioglitazone HCl and metformin HCl can be a better alternative way to conventional dosage forms.